MULTIASPECT SUSTAINABILITY ASSESSMENT OF FREIGHT TRANSPORTATION TOWARDS NET ZERO EMISSIONS : A STRATEGIC CASE STUDY OF JIIPE SPECIAL ECONOMIC ZONE, INDONESIA - Hidayati, Ratna; I Wayan Budiasa; Irman Firmansyah (Journal of Sustainable Finance and Development, 2026)
Freight transportation serves as the backbone of industrial growth but remains a primary driver of carbon emissions, posing a significant challenge to global climate goals. This study critically evaluates the multi-aspect sustainability status of freight transport within the Java Integrated Industrial and Ports Estate (JIIPE) Special Economic Zone (SEZ) Gresik, Indonesia, as a strategic hub for achieving Net Zero Emissions (NZE). Utilizing the Multiaspect Sustainability Analysis (MSA) framework and the Rapid Appraisal for Logistics Sustainability (RALS) technique, this research integrates four core dimensions: economic, social, environmental, law and governance. Data were synthesized from deep-dive stakeholder engagement and multi-criteria expert appraisal. The findings indicate a composite sustainability index of 58.91, categorizing the system as Sustainable. While economic performance excels (61.63), the environmental (60.50), law and governance (59.38), and social (54.13) dimensions exhibit critical deficits due to high fossil fuel dependency and lagging electrification infrastructure. Sensitivity analysis reveals that supply chain digitalization and fleet electrification are the most potent leverage factors. Monte Carlo simulations confirm result stability with a variance of less than 2.0%. To bridge the sustainability gap, this paper proposes a progressive policy framework involving localized carbon pricing and green financing incentives to accelerate industrial decarbonization by 2050.